Satisfaction and quality provided by students in dental clinics at private universities in northwestern Peru - Vergara Sánchez, Rufina Alicia; Solórzano Álvarez, Verónica Raquel; La Serna Solari, Paola Beatriz; Pinella Vega, Melissa (Horizonte Sanitario, 2025)
Objective: To analyze the relationship between patient satisfaction and the quality of care provided by undergraduate students in dental clinics at two private universities in northwestern Peru. Materials and methods: This was a basic, quantitative study with a non-experimental, correlational, descriptive, and cross-sectional design. The non-probability sample consisted of 134 patients. The data collection instruments were a Patient Satisfaction Questionnaire, previously submitted to expert review for content validation, and the Peruvian Ministry of Health (MINSA) Quality of Care Assessment Scale, both using a Likert-type scale.Results: The results indicated that the level of satisfaction was high, with an approval rating of over 98%, and that the quality of care was also positively valued by all participants. A significant correlation was observed in the 6th (Rho = 0.437; p = 0.042) and 7th (Rho = 0.514; p = 0.009) cycles in Chiclayo, as well as in the 6th (Rho = 0.567; p = 0.005), 7th (Rho = 0.450; p = 0.016) and 8th (Rho = 0.518; p = 0.040) cycles in Piura, indicating a progressive improvement in the perception of quality as the students' clinical training progresses.Conclusions: A significant association was found between satisfaction and quality of care among patients treated by dental students (p=.000; rho=.513). These findings suggest that the higher the perceived quality of care, the higher the levels of patient satisfaction, which reaffirms the importance of strengthening training and clinical processes in the university setting.Keywords: Attention; Quality; Satisfaction.